PENGHITUNGAN LINGKARAN TAHUN DENGAN EDGE LINKING DAN CHAIN CODE - Stephanus, Panji; Wahyuningrum, Shinta Estri (Universitas Katolik Soegijapranata, 2017)
Annual ring is growth ring which exists on tree trunk. Every year, this ring will expand and form new ring. These rings can be the standard to determine the age of a tree. This project aims to count the annual rings using edge linking adn chain code. The image of annual rings will be first converted to grayscale image, then applying median filtering process. And then doing the edge detection process then continued with edge linking. After finished, the next step is doing thresholding to separate the detected annual rings object with the background then count the rings using chain codennual rings object with the background then count the rings using chain code.